A novel frameshift GP1BB mutation causes autosomal dominant macrothrombocytopenia with decreased vWF receptor expression but normal platelet aggregation. (17th February 2022) - Dunstan-Harrison, Caitlin; Morison, Ian M.; Ledgerwood, Elizabeth C.
Abstract: GP1bβ is a component of the von Willebrand factor (vWF) receptor complex that is necessary for platelet formation and activation. A novel frameshift variant in GP1BB has been identified in a family with macrothrombocytopenia. The variant leads to a protein that is 101 amino acids longer than wild type with loss of the transmembrane domain. As there is no defect in platelet aggregation, the family are classified as heterozygous carriers of a Bernard–Soulier syndrome-related mutation. The levels of the vWF receptor on platelets are reduced to 50% of the controls, with the presence of large platelets but normal platelet aggregation demonstrating that decreased vWF receptor expression impacts proplatelet formation but not platelet function.